Cryptopygus antarcticus (Collembola) on some sub-Antarctic islands - O. V. Bezkrovna (Ukrainian Antarctic Journal, 2005)
Cryptopygus antarcticus was first found on some islands of the Argentine archipelago in 2000-2001. The finding was confirmed in 2005.